Upaya Meningkatkan Komunikasi dan Hasil Belajar Matematika dengan Strategi Active Knowledge Sharing pada Siswa - Azis, Azis; Nurlita, Maya; Sarmin, Alisa (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
The purpose of this study was to determine the improvement of mathematics learning communication during the learning process through the application of Active Knowledge Sharing strategies in class X students of SMK Negeri 1 Batauga and to determine the improvement of mathematics learning outcomes during the learning process through the application of Active Knowledge Sharing strategies in class X students of SMK Negeri 1 Batauga. This type of research is class action research. The implementation of this class action research consisted of two cycles. The subjects in this study were teachers and researchers, and the object of this research was class X students of SMK Negeri 1 Batauga totaling 15 people. The procedure of this class action research: 1) planning, 2) action implementation, 3) observation, 4) evaluation, and 5) reflection. Data collection techniques in this study were observation, tests, and documentation. The results of the research obtained through observation, evaluation, and reflection. Based on the results of the analysis and discussion, it can be concluded that there is an increase in mathematics learning communication after learning with active learning strategies of the Active Knowledge Sharing type in class X students of SMK Negeri 1 Batauga and there is an increase in mathematics learning outcomes after learning with active learning strategies of the Active Knowledge Sharing type in class X students of SMK Negeri 1 Batauga.